THE EFFECT OF PHYSICAL EDUCATION LEARNING SCHEDULE, FACILITIES, AND MOTIVATON ON LEARNING OUTCOMES OF EIGHTH GRADE STUDENT - Bambang Hariri; Moch Asmawi; Yasep Setiakarnawijaya (Gladi : Jurnal Ilmu Keolahragaan, 2021)
The purpose of this study was to obtain information about the effect of physical education learning. The method in this study used path analysis. The sample included in this study amounted to 80 students. The results of the analysis show that the contribution of the Physical Education Learning Schedule (X1) to Physical Education Learning Outcomes (Y) is significant at 0.761. , Learning Facilities (X2) on Learning Outcomes (Y) which is significant at 0.687, Motivation (X3) on learning outcomes (Y) which is significant at 0.677 , Physical Education Learning Schedule (X1) on Motivation (X3) which is significant at 0.420 , Learning Means (X2) on Motivation (X3) which is significant at 0.401. The conclusion in this study is that physical education learning schedule, learning facilities and motivation both have a direct effect on physical education learning outcomes. Physical education learning schedule, learning facilities have a direct effect on students' motivation.